Disconnected - Craig, Karly; Patterson, Nick; Copeland, James; Curtis, Katherine; Mills, Kenia (My University, 2016)
Credits: Director-Karly Craig. Producers-Nick Patterson, James Copeland. Director of Photography-Nick Patterson. Writers-James Copeland, Karly Craig, Katherine Curtis, Kenia Mills, Nick Patterson. Editing- James Copeland, Karly Craig, Katherine Curtis, Nick Patterson. Cast-Danielle Golway, James Copeland, Karly Craig, Kenia Mills, Kelsey Horn, Anthan Swearingen, Sam Welch, Zach Bird. Music-APM Music, “Half Speed,” “Coloured Warmly,” “Aerial and Spherical.”
Citation: 48-Dominate. (2016). Disconnected. K-State 48 Film Festival, 2016
Keywords: 48-Dominate; K-State 48 Film Festival